Intentions and reflections: the nature of legislative intent revisited - Ekins, R (Oxford University Press, 2019)
This article reflects on the argument of The Nature of the Legislative Intent, replying in part to thoughtful comments and criticisms made by contributors to this symposium. The reply opens by considering the methodology that underpins the book and the choices made in its deployment. The focus on the central case of legislative action is grounded in sound philosophy, which recognizes the explanatory priority of good reasons over bad. Reflecting on the moral need for legislation helps to articulate the internal point of view of the reasonable legislator, from which perspective the structure of legislative action is made clear. Likewise, reflection on the social ontology of group action confirms that legislators are able to act jointly to make reasoned choices together despite disagreeing about what ought to be done. The legislative assembly represents the people, leading and sharpening a public conversation about the common good. In enacting a statute, the legislature articulates a lawmaking choice by uttering the statutory text in its context. Interpreters can and should infer the legislature’s intentions in enactments and skepticism about the relevance of legislative intentions to statutory interpretation is unwarranted.